2023
DOI: 10.3390/antiox12122118
|View full text |Cite
|
Sign up to set email alerts
|

Potential Hepatoprotective Effects of Chamaecyparis lawsoniana against Methotrexate-Induced Liver Injury: Integrated Phytochemical Profiling, Target Network Analysis, and Experimental Validation

Eman Fikry,
Raha Orfali,
Shaimaa S. El-Sayed
et al.

Abstract: Methotrexate (MTX) therapy encounters significant limitations due to the significant concern of drug-induced liver injury (DILI), which poses a significant challenge to its usage. To mitigate the deleterious effects of MTX on hepatic function, researchers have explored plant sources to discover potential hepatoprotective agents. This study investigated the hepatoprotective effects of the ethanolic extract derived from the aerial parts of Chamaecyparis lawsoniana (CLAE) against DILI, specifically focusing on MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…Studies have shown that clethodim is reproductively toxic to zebrafish and induces neurological dysfunction in this model organism ( Wang et al, 2019 ; Xiong et al, 2019 ). Methotrexate, which exerts cytotoxic effects through the induction of inflammation and oxidative stress and causes lung damage and hepatotoxicity, was similarly found to be downregulated following treatment with 4,4′-methylenediphenol ( Fikry et al, 2023 ; Rajizadeh et al, 2024 ). The above observations indicated that the 4,4′-methylenediphenol-induced changes in metabolite abundance have an overall positive effect on neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that clethodim is reproductively toxic to zebrafish and induces neurological dysfunction in this model organism ( Wang et al, 2019 ; Xiong et al, 2019 ). Methotrexate, which exerts cytotoxic effects through the induction of inflammation and oxidative stress and causes lung damage and hepatotoxicity, was similarly found to be downregulated following treatment with 4,4′-methylenediphenol ( Fikry et al, 2023 ; Rajizadeh et al, 2024 ). The above observations indicated that the 4,4′-methylenediphenol-induced changes in metabolite abundance have an overall positive effect on neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%